A Case Study on Petronas Carigali Sdn Bhd (Facing the International Challenges) - Wan Muda, Wan Zainuddin (1997)
It was envisaged that globalisation of the world economy in terms of trade and investment would become more evident with rapid advancements in transport, communication and information technologies. As the twenty-first century approaches, the world would undergoing enormous change, a process of great upheaval and great possibility. In just a few short years, we have witnessed the dawn of post-industrial society, the advent of the information age, the rush to computerisation and therefore intensity competition. The increasing trend towards regionalism in trade and economical relationships would make it more imperative for small open economies like Malaysia to adapt effectively and speedily to the consequent challenges to maintain their comparative position. International competitiveness would be a moving target. However, it has the underpinning objective of maximising and increasing productivity as well as efficiency. Business environment has grown dramatically more intense including in Malaysia, and competition has become more global and more energised. And technology races on. No longer could business safely ignore their customer's wants and needs. No longer could personal relationships be granted. No longer could so much human creativity go so scandalously untapped.